Strategi Coping Nilai Akademik Pada Mahasiswa Salah Jurusan - Ainur Rohmah; Fatimah Azzahrah (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2021)
Wrong majors often provoke stress because they are obliged to learn that is not following the readability of students. On the other hand, the campus demands that we get good grades to pass the courses taken. The purpose of this paper is to determine the effect of coping strategies on students in the wrong major, determine the impact of self-efficacy on students in the wrong major, and determine the result of coping strategies and self-efficacy on students in the wrong major. The research method used is qualitative with interview data collection techniques on active students of IAIN Surakarta in the fourth semester and taking majors that are not following their interests and talents. The results showed that students used problem-focused coping and emotional-focused coping in overcoming the existing stress. In addition, they also create confidence in their self-efficacy to be able to survive in the department. This paper emphasizes for students in the wrong major to carry out good coping strategies according to their problems and not feel inferior to their abilities.